The Great Transition - Neizert, Eva; Spratt, Stephen (Ökologisches Wirtschaften - Fachzeitschrift, 2010)
Creating a new kind of economy is crucial if we want to tackle climate change and avoid the mounting social problems associated with the rise of economic inequality. The study ‘The Great Transition’ provides the first comprehensive blueprint for building an economy based on stability, sustainability and equality.
Keywords: Transition